2009
DOI: 10.1115/1.4000078
|View full text |Cite
|
Sign up to set email alerts
|

A Methodology to Analyze Changes in Lipid Core and Calcification Onto Fibrous Cap Vulnerability: The Human Atherosclerotic Carotid Bifurcation as an Illustratory Example

Abstract: A lipid core that occupies a high proportion of the plaque volume in addition to a thin fibrous cap is a predominant indicator of plaque vulnerability. Nowadays, noninvasive imaging modalities can identify such structural components, however, morphological criteria alone cannot reliably identify high-risk plaques. Information, such as stresses in the lesion's components, seems to be essential. This work presents a methodology able to analyze the effect of changes in the lipid core and calcification on the wall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 56 publications
2
36
0
Order By: Relevance
“…Maximum stresses in the plaque have been found at the shoulders by several investigators (Li et al 2006;Gao et al 2009;Kiousis et al 2009;Creane et al 2010); here, we see that changing the fibre configuration within the healthy arterial wall significantly alters the stress in these critical locations of the plaque (see Fig. 7).…”
Section: Healthy Versus Diseased Fibre Configurationmentioning
confidence: 79%
See 2 more Smart Citations
“…Maximum stresses in the plaque have been found at the shoulders by several investigators (Li et al 2006;Gao et al 2009;Kiousis et al 2009;Creane et al 2010); here, we see that changing the fibre configuration within the healthy arterial wall significantly alters the stress in these critical locations of the plaque (see Fig. 7).…”
Section: Healthy Versus Diseased Fibre Configurationmentioning
confidence: 79%
“…The identification of plaques vulnerable to rupture prior to the onset of symptoms would have major clinical advantages. Several studies have attempted to correlate the stresses within the plaque to its vulnerability using patient-specific finite element (FE) analyses (Li et al 2006;Tang et al 2008;Gao et al 2009;Kiousis et al 2009;Creane et al 2010). A significant limitation of many of these studies (Li et al 2006;Tang et al 2008;Gao et al 2009;Creane et al 2010) is the use of an isotropic material model given that it is known that the arterial wall behaves anisotropically (Rhodin 1980;Patel et al 1969;Holzapfel et al 2002) and since this may significantly alter the predicted stresses (Rodriguez et al 2008).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…It turns out that the resulting distributions of the wall stresses are strongly dependent on the stent design, and it was shown how a stent design should be modified to reduce the maximum wall stresses. In addition, Kiousis et al (2009) proposed a computational methodology to analyse the effect of changes in the lipid pool and calcification on wall stresses and on the collagenous cap vulnerability in a human carotid bifurcation. They found a positive correlation between the increase of lipid pool and the mechanical stress in the collagenous cap, and hence an increased risk of cap rupture.…”
Section: Modelling Fibre Dispersionmentioning
confidence: 99%
“…Carotid plaque vulnerability to rupture has been reported to be associated with stroke and other cerebrovascular events [11,12,13] and a lipid core with a thin fibrous cap that occupies a high proportion of the plaque volume is a predominant indicator of plaque vulnerability [14]. It has been reported that cerebral events can be precipitated by plaque rupture resulting from fibrous cap foam cell infiltration and cap thinning, similar to the mechanism of coronary plaque rupture leading to myocardial events [15].…”
Section: Introductionmentioning
confidence: 99%